Pengaruh Sertifikasi Halal, Religiusitas, dan Halal Awareness terhadap Minat Beli Konsumen UMKM - Hari Santoso Wibowo; Rianda Atmaja; Isa Saleh; Taufikkurrohman, Diki (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2025)
This study examines the influence of halal certification, religiosity, and halal awareness on the purchase intention of small, micro, and medium enterprises (UMKM) products at Masjid Salman ITB. Using a quantitative approach, this research involved 110 respondents as a sample and employed Smart PLS 3 as the analytical tool. The results indicate that all three independent variables have a positive and significant impact on purchase intention. The halal certification of Masjid Salman ITB serves as a halal assurance that enhances consumer trust, while the level of religiosity strengthens preferences for halal products. Additionally, halal awareness encourages consumers to be more selective in choosing products that align with Islamic values. These findings emphasize the importance of halal aspects in UMKM marketing strategies to enhance competitiveness and consumer trust.